2014
DOI: 10.1007/s10646-014-1236-4
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation and speciation of selenium in fish and insects collected from a mountaintop removal coal mining-impacted stream in West Virginia

Abstract: A major contaminant of concern for mountaintop removal/valley fill (MTR/VF) coal mining is selenium (Se), an essential micronutrient that can be toxic to fish. Creek chubs (Semotilus atromaculatus), green sunfish (Lepomis cyanellus), and composite insect samples were collected in March-July, 2011-2013 at two sites within the Mud River, West Virginia. One site (MR7) receives MTR/VF coal mining effluent, while the reference site (LFMR) does not. MR7 water had significantly higher concentrations of soluble Se (p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 35 publications
4
52
2
Order By: Relevance
“…Both Ni and Se were observed as trace levels. Mean Se levels were below USEPA surface water quality standards, which is worth noting as recent studies have shown adverse biological effects correlated with Se and its bioaccumulation (Farag et al, 1998;Clements 2004;Lindberg et al, 2011;Arnold et al, 2014). In general, it is likely that inorganic ions associated with UHW sites are the results of surface runoff associated with urbanization as well as organic compounds in-stream, while mining influence varied with surface/underground sourcing.…”
Section: Discussionmentioning
confidence: 93%
“…Both Ni and Se were observed as trace levels. Mean Se levels were below USEPA surface water quality standards, which is worth noting as recent studies have shown adverse biological effects correlated with Se and its bioaccumulation (Farag et al, 1998;Clements 2004;Lindberg et al, 2011;Arnold et al, 2014). In general, it is likely that inorganic ions associated with UHW sites are the results of surface runoff associated with urbanization as well as organic compounds in-stream, while mining influence varied with surface/underground sourcing.…”
Section: Discussionmentioning
confidence: 93%
“…The Mud River splits into 2 forks, referred to in the present study as specific sites on the main stem Mud River (MR7) and Left Fork Mud River (LFMR; Figure 1). Naming conventions are in keeping with previously published research [8,9]. The Left Fork and the main stem Mud River are connected via the Mud River Reservoir, allowing fish to migrate between these sites.…”
Section: Sampling Sitesmentioning
confidence: 99%
“…Symptoms of Se toxicity in fish include reproductive failure, teratogenesis, and increased mortality of early life stages [4][5][6]. Mountaintop removal/valley fill coal mining is a type of surface mining practiced throughout the Appalachian coal region that facilitates the release of Se from spoil rock into surrounding streams and rivers [7][8][9]. Mountaintop removal/valley fill coal mining is a type of surface mining practiced throughout the Appalachian coal region that facilitates the release of Se from spoil rock into surrounding streams and rivers [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the majority of studies have focused on invertebrate species, several studies have described a range of potential sub-lethal impacts in fish, which are related to coal mine discharge. These include effects on survival (Scullion and Edwards, 1980;Mylliemngap and Ramanujam, 2012), community structure (Branson and Batch, 1971;Daniel et al, 2014), morphometrics Banerjee, 2013, 2014), metal uptake (Bharti and Banerjee, 2011;Arnold et al, 2014), genotoxicity (Benassi et al, 2006), reproduction (Rudolph et al, 2008), metabolism (Miller et al, 2009) and oxidative stress (Benassi et al, 2006). However, research pertaining to native Australian fish species has been extremely limited, particularly considering the national importance of the mining industry.…”
Section: Introductionmentioning
confidence: 99%